6(2x-2)=3x-30

Simple and best practice solution for 6(2x-2)=3x-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-2)=3x-30 equation:


Simplifying
6(2x + -2) = 3x + -30

Reorder the terms:
6(-2 + 2x) = 3x + -30
(-2 * 6 + 2x * 6) = 3x + -30
(-12 + 12x) = 3x + -30

Reorder the terms:
-12 + 12x = -30 + 3x

Solving
-12 + 12x = -30 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-12 + 12x + -3x = -30 + 3x + -3x

Combine like terms: 12x + -3x = 9x
-12 + 9x = -30 + 3x + -3x

Combine like terms: 3x + -3x = 0
-12 + 9x = -30 + 0
-12 + 9x = -30

Add '12' to each side of the equation.
-12 + 12 + 9x = -30 + 12

Combine like terms: -12 + 12 = 0
0 + 9x = -30 + 12
9x = -30 + 12

Combine like terms: -30 + 12 = -18
9x = -18

Divide each side by '9'.
x = -2

Simplifying
x = -2

See similar equations:

| 2(x+12)-2x=(x-2) | | 29x=870 | | k/11=-11 | | 3m+16-2m=3 | | AX+BX-12=11 | | (50+X)(75+2X)=8568 | | x/18=8 | | B-6+4b=17 | | 4y-6x-9=0 | | 5(x+5)=2(8+2x) | | 6x-11=-8+9-6x | | -12=x-2 | | -9+x=5-8 | | 4x+3y=1450 | | -12=m+6 | | (14+x)= | | 20k-6k-8k= | | 6x-1=-8+9-6x | | 22x+4=14 | | -3m+10=-14 | | 32=12-v | | 26=9x+5-6x | | (50+X)(75+2X)=9375 | | n-4=-15 | | 1130-720f=382 | | 40-80d=c | | 3+1+x=12 | | 2(x-7)-10=12-4x | | 2(8+2x)= | | 28+2=n+22 | | 0=-18+v | | 3m^2+8m+15= |

Equations solver categories